RNA Detection in Live Bacterial Cells Using Fluorescent Protein Complementation Triggered by Interaction of Two RNA Aptamers with Two RNA-Binding Peptides - Charles R. Cantor; Natalia E. Broude; Paul Toran; Hung-Wei Yiu; Vadim V. Demidov (MDPI AG, 2011)
Many genetic and infectious diseases can be targeted at the RNA level as RNA is more accessible than DNA. We seek to develop new approaches for detection and tracking RNA in live cells, which is necessary for RNA-based diagnostics and therapy. We recently described a method for RNA visualization in live bacterial cells based on fluorescent protein complementation [1-3]. The RNA is tagged with an RNA aptamer that binds an RNA-binding protein with high affinity. This RNA-binding protein is expressed as two split fragments fused to the fragments of a split fluorescent protein. In the presence of RNA the fragments of the RNA-binding protein bind the aptamer and bring together the fragments of the fluorescent protein, which results in its re-assembly and fluorescence development [1-3]. Here we describe a new version of the RNA labeling method where fluorescent protein complementation is triggered by paired interactions of two different closely-positioned RNA aptamers with two different RNA-binding viral peptides. The new method, which has been developed in bacteria as a model system, uses a smaller ribonucleoprotein complementation complex, as compared with the method using split RNA-binding protein, and it can potentially be applied to a broad variety of RNA targets in both prokaryotic and eukaryotic cells. We also describe experiments exploring background fluorescence in these RNA detection systems and conditions that improve the signal-to-background ratio.